Сonfirmatory study of the efficacy and tolerability of trifluridine/tipiracil (TAS-102) therapy in the Russian population with chemorefractory metastatic colorectal cancer - M. Yu. Fedyanin (Медицинский совет, 2020)
Introduction. Trifluridine/Tipiracil (FTD/TPI) is a new chemotherapeutic drug approved in more than 60 countries for use in patients with metastatic colorectal cancer who have registered progression or intolerance to treatment with fluoropyrimidines, oxaliplatin and irinotecan, anti-VEGRand anti-EGFR-targeted agents. This study evaluated for the first time the effectiveness and tolerability of FTD/TPI therapy in the Russian patient population.Materials and methods. A confirmatory open-label single-arm non-randomized trial was conducted in 2 clinical centres in Russia. The main criteria for inclusion were: conduction of at least the 2nd line of standard systemic therapy for metastatic colon adenocarcinoma. The primary efficacy criteria were: 2-month progression-free survival; secondary – median progressionfree survival, disease control frequency, safety assessment, overall survival. Research number: NCT03274882.Results. A total of 26 patients were included in the study; the median age was 60.5 years (30 to 78); 19 (73%) women; and 4 patients with ECOG 0 and 22 – with ECOG 1. All patients were previously treated with the inclusion of oxaliplatin, irinotecan, fluoropyrimidines, 21 (81%) – bevacizumab, 6 (23%) – anti-EGFR antibodies, and 2 (7.7%) – regorafenib. The median for treatment courses was 4 (1–21), 11 (42.3%) patients were treated for 6 months or more. The two-month progression-free survival rate was 52% with a median progreesion-free survival rate of 4 months (95% CI 1.8–7.4 months). The median of total survival rate was 11 months (95% CI 5,2–16,8 months). Disease control was achieved in 60%. Neutropenia, nausea, vomiting, anemia, weakness prevailed among undesirable events associated with treatment (≥5 patients). The majority of complications were of the 1st–2nd degree. Among the undesirable events of the 3rd–4th degree, neutropenia was more common, while in 3 patients febrile neutropenia of the 3rd degree was registered.Conclusions. In the Russian population of patients with colorectal chemorefractory cancer, the drug FTD/TPI (TAS-102) shows efficacy and tolerability comparable to the RECOURSE registration study.